Comparing crime reporting factors in EU countries - Gallo de Puelles, Pedro (European journal on criminal policy and research, 2021)
Through crime-reporting citizens make their security needs explicit to the police. This information helps the police in the allocation of resources. In the European Union, there are significant differences among countries, both in terms of overall and specific crime-reporting rates. Factors highlighted by the literature that might explain these differences are not entirely satisfactory (...